“PROBLEMS IN A MULTILINGUAL ENVIRONMENT” - Maxamadova Zilola; Pardayev To'lqin (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article examines the challenges that arise in multilingual environments where people from diverse linguistic backgrounds interact. While multilingualism promotes cultural richness and broader communication, it also creates barriers in education, workplace communication, social integration, and policy- making. By analyzing these problems and suggesting possible solutions, this paper emphasizes the importance of developing inclusive strategies to ensure effective interaction in multilingual societies.